Gambaran Tentang Kemampuan Bersosialisasi pada Karyawan : Sebuah Kajian di Institusi Pendidikan Tinggi - Maharani, Anita; Srikandi, Anggara Bakti (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
Social relationships in the work environment is one source of job satisfaction. Work environment is employees place to have a socialization. Work environment is a major focus social bond formation, as employees find opportunities and legitimize the intent to find something new. Organization or educational institution is also the social sphere. Educational institutions can be defined as an organization that was founded and is run with the aim to become a place of development and dissemination of education, which of course depends on the segmentation of the intended participants. Type of the research is descriptive study, the purpose of this study was to see the preliminary description of social skills at an employee of a PT. X. The study population, is 130 people. Samples were selected by Non-Probability Sample techniques. Sampling mode with purposive sampling. Purposive sampling was conducted on the basis of considerations that researchers consider only the desired elements have been present in samples taken member. Thus, the sample in this research is 57 people. This research data collection method is by questionnaire. Data collection instrument of this research is to scale, ie, Likert scale. Results obtained in this study has not been able to prove the depth of social competence, although some may be disclosed allegations of social competence, such behavior will not give a hasty assessment of something, which is reflected in the statement